Hyponatremia in cancer patients: Strategy for safe correction in the hospital. Issue 3 (October 2019) - Chen, Sheldon
Hyponatremia is a common but challenging disorder to treat. The pathogenesis and the workup can be unexpectedly complicated, and the available therapies are manifold. Instead of trying to wrangle all of the aspects of hyponatremia into a comprehensive algorithm, we describe a general strategy that goes back to the first principles embodied in the model discovered by Edelman and colleagues back in 1958. The so-called Edelman equation underpins our modern understanding of [sodium] disorders, and it has engendered pretty much all of the [sodium] equations that are in clinical use. As the dysnatremias have a quantitative basis, a numerical approach seems prudent. We developed a predictive [sodium] equation that simultaneously considers all of the ongoing inputs and outputs of Na/K/H2 O that would perturb the serum [Na] and also factors in the element of time that would determine the rate of [Na] correction. Our equation solves for the rate of intravenous fluid (or salt tablet) administration, because that information helps clinicians the most when prescribing therapy for inpatients. With the rate of [Na] correction built in, the equation also aims to safeguard against overcorrection. Since the equation is programmable into a clinical calculator, our renal fellows find it easy to use on their own. However, all of the [sodium] equations are fallible, because their data are no longer valid when the clinical parameters change, as they are likely to do. Nevertheless, we believe that the quantitative approach to hyponatremia has much to offer in terms of efficacy and safety.